2018
DOI: 10.1002/jso.25080
|View full text |Cite
|
Sign up to set email alerts
|

The association of renal cell carcinoma with gastrointestinal stromal tumors

Abstract: Background and Objectives Prior small studies have reported a possible association between renal cell carcinoma (RCC) and gastrointestinal stromal tumors (GISTs). In the largest known series, our objective was to describe the prevalence of RCC among patients with GISTs over 26 years at Memorial Sloan Kettering Cancer Center (MSKCC). Methods We retrospectively reviewed MSKCC’s prospectively maintained sarcoma and RCC databases and identified all patients with both RCC and GIST between 1980 and 2016. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…The frequency of synchronous or metachronous SPTs in patients with GIST, is widely variable among different studies published in the literature [11,13,14,16]. In the present study, a frequency of 17.9% has been detected, while our overview of systematic reviews shows that the cumulative prevalence rate of SPTs ranges from 9.3% in the study by Agaimy et al [7] to 18.0% in the study by Diamantis et al [24], with a mean prevalence rate of 14.5%.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…The frequency of synchronous or metachronous SPTs in patients with GIST, is widely variable among different studies published in the literature [11,13,14,16]. In the present study, a frequency of 17.9% has been detected, while our overview of systematic reviews shows that the cumulative prevalence rate of SPTs ranges from 9.3% in the study by Agaimy et al [7] to 18.0% in the study by Diamantis et al [24], with a mean prevalence rate of 14.5%.…”
Section: Discussioncontrasting
confidence: 38%
“…Outside of these syndromic forms, little is known about the sporadic coexistence of GISTs with SPTs, although multiple single institution and population-based studies have reported GIST patients to have an increased risk of presenting with additional malignancies, either synchronously or during follow-up [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the three cases, two were CRCC, and the radiological features of the third were suggestive of papillary RCC. This is not surprising as papillary RCC prevalence in GIST patients is much proportionally higher 14,23 . The GISTs in our GU cancer patients were incidental during planned nephrectomy or adrenalectomy.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 69 articles were reviewed. Seventeen articles reported the prevalence of genitourinary cancer associated with GIST ranging 2.1-15.6% (Table 2) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Prostatic adenocarcinoma was the most common primary genitourinary cancer (2.1-14%), followed by RCC (0.6-11.4%).…”
Section: Resultsmentioning
confidence: 99%